Olive oil quality identification device based on three-dimensional fluorescence characteristic peak - DING ZHIQUN (2021)
The utility model belongs to the technical field of edible oil detection, and provides an olive oil quality identification device based on a three-dimensional fluorescence characteristic peak, which comprises a light source used for exciting fluorescence of a preset olive oil sample; a plurality of optical filters with preset wavelengths are arranged in the optical filter wheel, and the optical filter wheel is used for filtering fluorescence generated by the preset olive oil sample into fluorescence with different wavelengths; the photoelectric detector is used for collecting the filtered fluorescence spectrums with different wavelengths and converting the collected fluorescence spectrums into electric signals; and the microprocessor is used for calculating the olive oil quality factor according to a preset fluorescence integral ratio algorithm by using the processed electric signal. Compared with other three-dimensional fluorescence spectrum combined chemometrics algorithms, the olive oil quality identificat